2018
DOI: 10.1016/j.bjps.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Surgical-site infection following lymph node excision indicates susceptibility for lymphedema: A retrospective cohort study of malignant melanoma patients

Abstract: SSI was the greatest independent risk factor for developing lymphedema. Additionally, patients' that developed postoperative seroma were at an increased risk of also developing SSI. Future studies should examine if lymphedema can be prevented, by reducing seroma and SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
0
17
0
3
Order By: Relevance
“…Hence, the 2x10Gy model is a Refinement of previous works, in that no serious morbidity was observed and allows for lymphedema to be consistently quantifiable with a Reduced number of animals [33]. While the described mouse model shares many of the key clinical lymphedema characteristics, the etiology of the condition is different to the long-term onset seen in humans [34]. As rodents primarily heal by contraction and humans by reepithelization [35], no lymphedema rodent model can resemble the human condition perfectly.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, the 2x10Gy model is a Refinement of previous works, in that no serious morbidity was observed and allows for lymphedema to be consistently quantifiable with a Reduced number of animals [33]. While the described mouse model shares many of the key clinical lymphedema characteristics, the etiology of the condition is different to the long-term onset seen in humans [34]. As rodents primarily heal by contraction and humans by reepithelization [35], no lymphedema rodent model can resemble the human condition perfectly.…”
Section: Discussionmentioning
confidence: 96%
“…One of the most common postoperative complications in the perioperative period is seroma. 1,10,11 There have been multiple studies that have investigated interventions designed to either reduce the incidence or reduce the extent of the problem once it has become established. [12][13][14][15] A recent systematic review by the Cochrane Group 11 identified a lack of any useful data and concluded that, ''…there is a need for high quality RCTs to guide clinical practice in this under-researched area.''…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown an associated increase in lymphoedema with postoperative surgical site infection. 10 , 15 It is advocated that any future randomised study should include lymphoedema as an endpoint. Finally, it is worth commenting that the median length of stay was 8 days for both cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection of malignant melanoma that has metastasized must also be accompanied with complete lymph node dissection. However, there is a marked increase in risk of lymphedema due to a cascade of postoperative events (Jørgensen et al, 2018). Systemic adjuvant therapy, especially targeted combination therapy, might offer significant advantages in the treatment of melanoma.…”
Section: Introductionmentioning
confidence: 99%